2022
DOI: 10.1111/cogs.13169
|View full text |Cite
|
Sign up to set email alerts
|

Simplicity as a Cue to Probability: Multiple Roles for Simplicity in Evaluating Explanations

Abstract: People often face the challenge of evaluating competing explanations. One approach is to assess the explanations’ relative probabilities–for example, applying Bayesian inference to compute their posterior probabilities. Another approach is to consider an explanation's qualities or “virtues,” such as its relative simplicity (i.e., the number of unexplained causes it invokes). The current work investigates how these two approaches are related. Study 1 found that simplicity is used to infer the inputs to Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…In addition to cautioning against characterizing one of these judgments in terms of another, our findings raise questions about the extent to which different kinds of explanatory and causal judgments could diverge. For instance, evaluating explanatory “goodness” could diverge from evaluations of explanation probability (see Vrantsidis and Lombrozo, in press ), just as evaluations of causal structure diverge from those of strength (e.g., Griffiths and Tenenbaum, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cautioning against characterizing one of these judgments in terms of another, our findings raise questions about the extent to which different kinds of explanatory and causal judgments could diverge. For instance, evaluating explanatory “goodness” could diverge from evaluations of explanation probability (see Vrantsidis and Lombrozo, in press ), just as evaluations of causal structure diverge from those of strength (e.g., Griffiths and Tenenbaum, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is more general evidence that explanatory judgments may be “special” and differ in various ways from other related judgments (see Lombrozo, 2012 ; Lombrozo and Vasilyeva, 2017 , for reviews). When people evaluate explanatory claims, they take into account such properties of explanatory hypotheses as simplicity (preferring simpler explanations even when probabilistic evidence favors complex explanations; Lombrozo, 2007 ; Bonawitz and Lombrozo, 2012 ; Pacer and Lombrozo, 2017 ; Vrantsidis and Lombrozo, in press ), latent scope (preferring explanations that do not make unverified predictions; Khemlani et al, 2011 ), explanatory power [roughly tracking confirmation, ( Good, 1960 ) while deviating from the objective posterior probability of a hypothesis; Douven and Schupbach, 2015a , b ] and other explanatory “virtues” ( Lipton, 2004 ). This illustrates that explanation judgments are influenced by a variety of considerations beyond the covariation between cause and effect.…”
Section: Introductionmentioning
confidence: 99%
“…By how much will a test question asking subjects to pick the most satisfying rather than the most probable explanation influence their explanatory choices? Two papers (Lombrozo, 2007;Vrantsidis & Lombrozo, 2022) have used and compared both types of test query formulations in experimental scenarios about diseases, where a satisfaction test query could be interpreted as a question asking for the more preferable outcome, e.g., having one rather than two diseases. These studies have found only small differences between the two kinds of test query formulations, which might mean that if there was this (mis-) interpretation of satisfaction test queries, it probably did not occur in many subjects (if many subjects did it, one would probability have observed very strong preferences for one disease over two in the satisfaction query conditions).…”
Section: Test Query Formulationmentioning
confidence: 99%
“…1. For example, in Vrantsidis and Lombrozo's (2022) experiments, subjects read a fictitious scenario about aliens from planet Zorg who can contract three different diseases: Tritchet's syndrome, which causes sore minttels and purple spots, Morad's disease, which causes only sore minttels, and a Humel infection, which causes only purple spots. The test case described an alien suffering from both sore minttels and purple spots.…”
Section: Test Query Formulationmentioning
confidence: 99%
See 1 more Smart Citation